2015
DOI: 10.1007/s10096-015-2461-3
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of TLR4 and TLR9 SNPs in protection against congenital toxoplasmosis

Abstract: The purpose of this investigation was the determination of the distribution of genotypes at single nucleotide polymorphisms (SNPs) of the toll-like receptor 4 (TLR4) and the toll-like receptor 9 (TLR9) in fetuses and newborns congenitally infected with Toxoplasma gondii and the identification of genetic changes predisposing to infection development. The study involved 20 fetuses and newborns with congenital toxoplasmosis and 50 uninfected controls. The levels of IgG and IgM antibodies against T. gondii, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The authors of a previous study reported that the TLR9 gene causes an intracellular receptor signal cascade, and thus evokes nuclear transcription factors resulting in the production of pro-and anti-inflammatory cytokines (Hemmi et al, 2000). The authors of previous studies have reported that TLR9 gene polymorphisms are associated with the development of several inflammatory diseases (Bharti et al, 2014;Berenson et al, 2015;Trejo-de la O et al, 2015;Wen et al, 2015;Wujcicka et al, 2015). Bharti et al (2014) conducted a study in a Chinese population and assessed the association between TLR9 polymorphisms and pulmonary tuberculosis; they found that the TLR9 rs187084 polymorphism was associated with reduced risk of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a previous study reported that the TLR9 gene causes an intracellular receptor signal cascade, and thus evokes nuclear transcription factors resulting in the production of pro-and anti-inflammatory cytokines (Hemmi et al, 2000). The authors of previous studies have reported that TLR9 gene polymorphisms are associated with the development of several inflammatory diseases (Bharti et al, 2014;Berenson et al, 2015;Trejo-de la O et al, 2015;Wen et al, 2015;Wujcicka et al, 2015). Bharti et al (2014) conducted a study in a Chinese population and assessed the association between TLR9 polymorphisms and pulmonary tuberculosis; they found that the TLR9 rs187084 polymorphism was associated with reduced risk of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…1), were genotyped, using the self-designed nested PCR-RFLP assays. The sequences of the external and internal primers, the lengths of PCR products and annealing temperatures, used in the PCR assays for TLR SNPs, were previously shown [18, 28, 44]. The sequences, annealing temperatures, and the sizes of amplicons for TLR SNPs are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Andrade et al [38] have demonstrated TLR7 and TLR9 sense T. gondii-associated nucleic acids (DNA or RNA) while TLR11 and TLR12 sense Toxoplasma profiling. Thus, understanding genomic variations in TLR is important to highlight immune defense against T. gondii [30,39,40]. NOD-like receptor (NLR) families are important for immediate responses against structures that are present in T. gondii like TLR receptors.…”
Section: Importance Of Human Genetic Variation For Toxoplasmosis Infementioning
confidence: 99%